Akkermansia muciniphila helps in the recovery of lipopolysaccharide-fed mice with mild intestinal dysfunction - Hu, Yue; Zhou, Jun; Lin, Xiaoqi (Frontiers in Microbiology, 2025)
BackgroundMild intestinal dysfunction, linked to subtle yet significant health issues, can be induced by lipopolysaccharide (LPS), a Gram-negative bacterial component that disrupts gut function and triggers inflammation. Akkermansia muciniphila has shown promise as a probiotic for gut health due to its roles in mucin degradation and short-chain fatty acid production. This study explores the therapeutic effects of Akkermansia muciniphila on LPS-induced mild intestinal dysfunction in mice.MethodsThirty-eight 6-week-old C57BL/6 mice were split into control (n = 19) and LPS-treated (n = 19) groups. LPS-treated mice received 300 μg/kg/day of LPS for 4 weeks, followed by Akkermansia muciniphila supplementation at 41 mg/kg/day (Akk1) or 82 mg/kg/day (Akk2) for another 4 weeks. Gut microbiota was analyzed via metagenomic sequencing, and gene expression was evaluated through transcriptomics.ResultsLPS significantly altered gut microbiota, reducing diversity and increasing pathogenic genera like Lachnoclostridium. Akkermansia muciniphila supplementation, particularly at higher doses, partially restored gut microbiota by increasing beneficial genera such as Muribaculum. Transcriptomics showed that LPS induced immune and inflammatory responses, while Akkermansia muciniphila reduced these effects by modulating pathways like TNF and NF-kappa B signaling.ConclusionAkkermansia muciniphila mitigates LPS-induced gut dysfunction by restoring microbiota balance and modulating immune responses, highlighting its potential as a therapeutic agent for gut health.